A new method based on heuristic evaluation and realistic simulation for the development of mechanical ventilators centered on the user interface - Nathalia Parente de Sousa Maia (2014)
Introduction: New human-machine interfaces have been developed to incorporate the new modes and ventilatory parameters. Multiple monitoring data and alarms are presented in graphical interfaces, which many consider still far from ideal for the primary users, healthcare professionals. Hypothesis: Noncompliance with the heuristic human machine interaction can compromise the usability of lung mechanical ventilators by users (doctors, nurses, physiotherapists) Objectives: To develop a new methodology for evaluating and implementing improvements on a ventilator interface pulmonary mechanical intensive care unit (ICU) second heuristic principles. Methods: An experimental study, using two methodologies: one centered on heuristic evaluation by an expert, and the second one focused on a comparative assessment by non-experts. Was held during the period from January 2013 to March 2014, the Laboratory of Respiratory (RespLab). The research was divided into three steps: 1st) evaluating the usability of six habilities (connect, adjust or alter ventilation modes and their parameters; adjust and react appropriately to different types of alarms, monitor respiratory mechanical parameters, and set the trigger mode non-invasive) ventilation interface for experts users; 2nd) Implementation of suggestions for improvements to the interface by a team of specialist engineers in mechanical ventilation (MV); 3rd) Comparison between interfaces (old and new), for users not experts, assessing six tasks (call, adjust the patient, adjust the volume control ventilation (VCV), measurement of mechanical, adjust the pressure control ventilation (PCV), pressure suport ventilation adjustment (PSV). The analysis of the 1st step was descriptive. The outcomes of the 3rd step were: executionÂs runtime and successes of tasks and usability score by analogic visual scale (AVS). Results: Step 1: Participants 8 professional experts. 93 problems were listed. The most violated principles: 5 (error prevention), 1 (Visibility of System Status) and 7 (Flexibility and efficiency of use). 2nd step: passed on and discussed all reports completed by experts users. Changes in the interface were performed following the suggestions and principles heuristics. 3rd step: VCV adjustment, mechanical ventilation and PSV adjustment required longer time to execute; p = 0.02 for the runtime of the task of connecting when first used, to the old interface; p = 0.02 for correct setting of PSV when first held in the new interface; p = 0.08 for the usability score, favoring the new interface. Conclusion: It was possible to develop a new methodology for evaluating and implementing improvements on a mechanical ventilator in ICU interface according to the heuristics.